The relationship between physical fitness levels, motivation to participate in physical education and physical activity attitudes of middle school students - Arslan Kabasakal Sema; Geri Serdar (SHS Web of Conferences)
This study investigates the relationship between physical fitness levels, motivation to participate in physical education lessons, and physical activity attitudes in middle school students. A total of 106 middle school students with an average age of 12.02±1.16 from Yalova province were included in the study. Physical fitness tests were performed on the participants, and they filled out the Physical Education Motivation Scale (PEMS) and the Physical Activity Attitude Scale for Children and Adolescents (PAASCA). Within the scope of the findings, significant differences were found in right and left flexibility, PEMS total score, intrinsic motivation sub-dimension score, and PAASCA total score according to gender (p<0.05). In contrast, no significant differences were found in other variables (p>0.05). No significant relationship was found between the physical fitness parameters of the participants and PAASCA scores and PEMS total and sub-dimension scores (p>0.05). A significant relationship was found between the PAASCA scores of the participants and the PEMS sub-dimension scores. As a result, as the intrinsic and extrinsic motivation to participate in physical education classes increases, the physical activity attitudes of middle school students improve. The level of physical fitness does not affect the motivation to participate in physical education lessons and the attitude to participate in physical activity of middle school students.*